Community as Locus for Health Formal and Non-Formal Education: The Significance of Ecological and Collaborative Research for Promoting Health Literacy - Pais, Sofia C.; Rodrigues, Mariana; Menezes, Isabel (Frontiers in Public Health, 2014)
The World Health Organization (2002) considers that a balance between government, community and individual action is necessary for health education and promotion, recognizing that nongovernmental organizations, local groups, and community institutions are central in this process. This argument reinforces the idea that individuals should be empowered and encouraged to make use of accurate health-related information. This paper highlights the potential of a socio-political perspective for the development of health literacy within children and adolescents, and presents two studies conducted in two daily life contexts: a community organization and a school. Both studies are based on methodological pluralism and collaborative research approaches and explore the promotion of health knowledge in formal and informal settings. Study 1 is based on a mixed methodology, using focus group discussions and questionnaires with children and youth with chronic diseases to explore the perceived impact of their participation in support associations. Study 2 presents four intensive case-studies in schools where adolescents used community profiling, a participatory research methodology, to explore health rights and access to healthcare in both a historical and prospective vision. The results enable a deeper understanding on how powerful tool ccommunity resources can be for individual and collective empowerment on health issues.